Sukcesja codzienności. Mechanizmy międzypokoleniowej transmisji stylów życia polskiej klasy średniej - Bielińska, Magdalena (Studia socjologiczne, 2024)
The main aim of this paper is to address the problem of intergenerational transmission of middle-class lifestyles in Poland. Lifestyle is considered as a cultural characteristic of social position, enabling the reproduction of the middle class. Through the research procedures, i.e., reanalysis of the interviews dating back two decades, research revisits to middle-class parents, and the interviews with their heirs, I make comparisons over time and between generations to determine trends in lifestyles. I identify the distinguished types of lifestyle transmission mechanisms (intentional, unintentional, imitative, habitual) in such aspects as parenting styles, educational and occupational aspirations, attitudes to propertyand money management modes. The results showed the existence of intergenerational transmission and the continuity of family-transmitted principles. The effort by middle-class parents to format their children’s lifestyles, found in the research data, may have important implications for the reproduction of this segment of the social structure.